Foreign Workers: Implementation and Administration in Thailand - Aenihon, Paksiri (Arts of Management Journal, 2018)
The Problem migrant worker was the main reason from economy, social and political. It resulted from transformation of Thailand and need a lot of workers. So, it happened brought up and trafficking. The government operation had weakness in litigation and suppression of illegal migrant workers problem and affected the solution in overall, lacking unity and efficiency of national security and peace of order social. But another sides of problem reflected importance of migrant workers to economic of Thailand. And industrial developed countries grew up by the migrant workers of other countries, who was mechanism to enhance economic growth of a country. In other words, we should not looking movement of transnational labour migrant workers in negative as labour migration was beneficial both of the living life of labour migration and economic of countries. At the end of this article, the authors had proposed about solution of the migrant workers problem. The result reveal that the method of migrant workers management by the government must been planning accordingly on short and long term and administrative migrant workers on moderately level and sufficiency to need labour migrations. Although, the government was accelerate educational reforms of Thailand associate with labour of market, who clued hidden problems in the policy and encourage creative solution of the problem.